2008
DOI: 10.1557/jmr.2008.0359
|View full text |Cite
|
Sign up to set email alerts
|

Formation of LuFe2O4 phase from an undercooled LuFeO3 melt in reduced oxygen partial pressure

Abstract: The formation of metastable phases from an undercooled LuFeO 3 melt was investigated under reduced Po 2 since the iron ion has the tendency to change its valence state from Fe 3+ to Fe 2+ in an ambient atmosphere with low Po 2 . The nucleation and the post-recalescence temperatures of the phases were decreased with decreasing process Po 2 . Phase equilibrium was established in the Lu-Fe-O system at 1473 K by varying the oxygen partial pressure from 10 5 to 10 −1 Pa. A possible ternary metastable phase diagram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…If three-dimensional (3D) island growth occurs, the RHEED images correspond to the diffraction pattern of the transmitted electron beam which contains more structural information. Figure 3 shows the RHEED images of the MgO (111) substrates and the LuFe 2 O 4 films with the electron beams directed along MgO [1][2][3][4][5][6][7][8][9][10] or MgO . The strong LuFe 2 O 4 (003), (006), and (009) peaks observed in Fig.…”
Section: B Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…If three-dimensional (3D) island growth occurs, the RHEED images correspond to the diffraction pattern of the transmitted electron beam which contains more structural information. Figure 3 shows the RHEED images of the MgO (111) substrates and the LuFe 2 O 4 films with the electron beams directed along MgO [1][2][3][4][5][6][7][8][9][10] or MgO . The strong LuFe 2 O 4 (003), (006), and (009) peaks observed in Fig.…”
Section: B Structural Characterizationmentioning
confidence: 99%
“…In this work, we start from the ternary phase diagram of the bulk Lu-Fe-O system, a section of which is shown in Fig. 1(a) at 1200 • C. 8,9 This system belongs to the D-type of lanthanoid-Fe-O compounds for which there are four stable three-element phases: LuFe 2 O 4 (A) and Lu 2 Fe 3 O 7 (B), LuFeO 3 (perovskite or P), and Lu 3 Fe 5 O 12 (garnet or G). 10 In principle, one way to form a single LuFe 2 O 4 phase is to keep atomic ratio Lu:Fe=1:2 and vary the O 2 pressure, as shown as a thick dashed line in Fig.…”
Section: A Growth Diagrammentioning
confidence: 99%
“…In agreement with ref. [33], the thermodynamic phase diagram (Figure S5, Supporting Information) constructed based on the calculated enthalpies of Fe 2 O 3 , Lu 2 O 3 , and LFO oxides indicates that the orthorhombic LFO structure is not stable, consistent with the depiction as a point in the ternary phase diagram, and can be stabilized by epitaxial growth.…”
Section: Resultsmentioning
confidence: 54%
“…LFO thin films with Lu/Fe ratios of 0.6, 0.8, 1.0, 1.2, and 1.5 were grown on (001)-oriented STO (insulating) and Nb-doped STO (NSTO, conductive) substrates with a = 3.905 Å (Figure 1a). There were no secondary phases observed in the wide angle range X-ray diffraction (XRD) scans (15°-80 o , Figure S1, Supporting Information) for any of the films, despite the fact that according to the Lu-Fe-O ternary phase diagram, [33] LFO does not accommodate significant excess Lu or Fe, instead forms additional phases such as LuFe 2 O 4 , Lu 3 Fe 5 O 12 , Lu 2 Fe 3 O 7 , hexagonal LuFeO 3 , or binary oxides when Lu/Fe differs from 1.0. Due to the ionic radius difference between Lu 3+ (86 pm) and Fe 3+ (60 pm), as the film becomes Lu-rich, the XRD peak position 2θ of (002) p (p denotes the pseudocubic notation) moves to a lower angle and the out-of-plane lattice parameter c p increases from 3.789 Å (Lu/Fe = 0.6), 3.793 Å (Lu/Fe = 0.8), 3.800 Å (Lu/Fe = 1.0), 3.820 Å (Lu/Fe = 1.2), to 3.846 Å (Lu/Fe = 1.5).…”
Section: Resultsmentioning
confidence: 99%
“…The reported magnetic transition temperature seems to be a little lower than the stoichiometric sample, which indicates the presence of small amounts of ionic vacancies. Kumar et al reported the presence of a LuFe 2 O 4 phase during the synthesizing of LuFeO 3 with a gas floating crystal growth method [127].…”
Section: Development In Chemical Approachmentioning
confidence: 99%